“Spectacular” User Subjectivities on Instagram: A Discursive Interface Analysis - Milioni, Dimitra L.; Kollyri, Lydia (My University, 2022)
Instagram has succeeded in becoming a pervasive part of everyday life for many of its million users. Drawing on the Debordian concept of the spectacle and principles of Actor Network Theory, we approach Instagram as a sociotechnical assemblage, examining how it functions as a norm-(re)producing mechanism and how it constructs user subjectivities, analyzing both the platform’s design and the surrounding discourses. Four types of “ideal” users are prescribed: (1) spectators, (2) producers of spectacular content, (3) sociable users, and (4) consumers of commodities and aspiring influencers. Based on this analysis, we argue that Instagram closely resembles a contemporary spectacle (“Spectacle 2.0”), whose key logic is the aestheticization of everyday life.
Keywords: Instagram; interface analysis; spectacle; ideal user; aestheticization